2013
DOI: 10.31018/jans.v5i2.332
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bioactive phytochemicals and evaluation of antioxidant activity of a medicinal plant, Boerhaavia diffusa L.

Abstract: Boerhaavia diffusa L. (Family: Nyctaginaceae) commonly known as Punarnava is an herbaceous, spreading vine widely distributed in the tropical and subtropical regions in the world. The plants are a rich source of vitamins, minerals, protein and carbohydrate. The present study was carried out to determine the concentration of some bioactive phytochemicals (ascorbic acid, carotenoids, total phenolics, protein and carbohydrate) and their antioxidant activity in punarnava. Results showed the values for ascorbic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…16 From the literature, concluded that the effect of various extracting solvents and its comparison on total phenolic content (TPC), total flavonoid content (TFC), total tannin content (TTC) and antioxidant potential in crude extract of root of B. diffusa is still paucity. 17,18 So, the aim of present work is evaluation of the solvent extraction process for B. diffusa root extract through the determination of its phenolic, flavonoid, tannin content, and antioxidant activity assay.…”
Section: Introductionmentioning
confidence: 99%
“…16 From the literature, concluded that the effect of various extracting solvents and its comparison on total phenolic content (TPC), total flavonoid content (TFC), total tannin content (TTC) and antioxidant potential in crude extract of root of B. diffusa is still paucity. 17,18 So, the aim of present work is evaluation of the solvent extraction process for B. diffusa root extract through the determination of its phenolic, flavonoid, tannin content, and antioxidant activity assay.…”
Section: Introductionmentioning
confidence: 99%